Promotion of Treg/Th17 balance in MRL/lpr mice by Jianpi-Zishen Formula via modulation of DNMT1-mediated Foxp3 methylation - Li, Ming; Pang, Lijun; Li, Yunfei; Chen, Junjie; Shang, Shuangshuang; Huang, Chuanbing (Frontiers in Immunology, 2025)
PurposeThis study aimed to investigate whether Jianpi-Zishen Formula (JPZS) modulates the Treg/Th17 balance in MRL/lpr mice through regulation of DNA methyltransferase 1 (DNMT1)-mediated forkhead box P3 (Foxp3) methylation, and to elucidate its potential mechanism for improving immune homeostasis in systemic lupus erythematosus (SLE).MethodsForty-eight female MRL/lpr mice were randomized into six groups (n=8/group): JPZS (low/medium/high doses), 5-aza-CdR (DNMT inhibitor), DC_517 (DNMT1 inhibitor), and model control. Eight C57BL/6 mice served as healthy controls. The mice were subjected to the corresponding intervention measures for eight weeks. The impact of JPZS on the disease progression of MRL/lpr mice was evaluated using enzyme-linked immunosorbent assay (ELISA) and serum biochemical parameters. Moreover, immunofluorescence staining and flow cytometry were employed to investigate alterations in the proportions of Tregs and Th17 cells. CD4+ T cells were isolated from the spleen for subsequent investigation, including quantitative real-time PCR, western blotting, and determination of DNA methylation levels. Furthermore, the enzymatic activity of CD4+ T cell-specific DNA methyltransferases was quantified using an EpiQuik DNMT detection kit.ResultsJPZS significantly improved the disease development of MRL/lpr mice in a dose-dependent manner. Flow cytometry and immunofluorescence indicated JPZS promoted Treg/Th17 rebalancing. Research has found that Foxp3 is at a high methylation level in CD4+ T cells of the model group, and the transcription level of Foxp3 mRNA is downregulated; JPZS can downregulate Foxp3 methylation levels of CD4+ T cells in the model group. Further research has found that the level of Foxp3 methylation is closely related to Dnmt1 enzyme activity, and JPZS can downregulate Dnmt1 enzyme activity, thereby upregulating the transcription level of Foxp3 mRNA.ConclusionJPZS may restore Treg/Th17 balance in SLE via DNMT1-regulated Foxp3 demethylation, suggesting an epigenetic mechanism for its immunomodulatory effects.